M35 Adverse Effects Of Latent Tuberculosis Treatment In Migrants. (10th November 2014) - Denneny, EK; Macavei, VM; Rolls, S; Ma, C; Jayasekera, NP; O'Shaughnessy, TC; Potter, VLC; White, VLC; Kunst, H
Abstract : Background: Most cases of tuberculosis (TB) in the UK occur in migrants. The majority develop active TB within 5 years of arriving in the UK, usually due to reactivation from latent tuberculosis infection (LTBI). Therefore identifying and treating LTBI in migrants who are at risk of reactivation, is critical to reduce rates of active TB. It is, however, unclear if migrants develop any significant adverse effects from chemoprophylaxis (Rifampicin and Isoniazid), which subsequently affects adherence. Aim: To assess the type and frequency of adverse effects in migrants on treatment for LTBI. Methods: A retrospective study was conducted within our Trust between 1st January 2007 and 31st December 2012. Records of patients between the ages of 16–35, who had lived in the country for less than 5 years and received chemoprophylaxis, were examined. Results: 472 patients treated for LTBI were included. Mean age was 30.4 ± 7.4 years and 54.8%(259) were males. Ethnic origin included: Indian subcontinent 327(69.3%), African 113(24%), Caucasian 14(3%) and other 18(3.8%). Hepatitis B was detected in 5 cases (1%), hepatitis C in 2 cases (0.4%) and HIV was present in 1 case (0.2%). 19(4%) patients experienced adverse effects. 13(2.7%) reported gastrointestinal symptoms (nausea, vomiting), 4(0.8%) developed a skin rash and there was 1(0.2%) case of thrombocytopenia. Three of the 4 cases who developed a skin rash stopped ATT, and all three patients developed active TB two to four years later. One patient developed peripheral neuropathy due to Isoniazid. Drug induced hepatitis with a rise in ALT greater than three times the upper limit of normal was present in 15 patients (3.1%). An increase in bilirubin level greater than two times normal was recorded in 5 patients (1%). One patient who had concurrent hepatitis B was hospitalised due to hepatotoxicity. Conclusion: Treatment for LTBI in migrants below the age of 35 is safe, associated with a low risk of hepatotoxicity and should be feasible in primary care. Adverse effects should be managed promptly to ensure treatment adherence and prevention of progression to active TB.